Sustainable Business Practices and Environmental Accounting: A Review Approach - Amardeep Bajpai (AG Volumes, 2025)
Growing global warming raises serious concerns about environmental sustainability. A company’s commitment to sustainability can be best demonstrated by adhering to green accounting practices and transparency. This article addressed the Environmental Accounting, its Importance and Advantages Importance of Sustainable Business Practices in Developing Nations. It highlights how integrating environmental costs and resource impacts into accounting enhances transparency, stakeholder trust, and decision-making. Evidence shows a positive link between environmental accounting and financial performance through cost savings and profitability, underscoring its strategic role in aligning economic goals with environmental responsibility and sustainable development.